2023
DOI: 10.1186/s40001-023-01523-7
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive review of the family of very-long-chain fatty acid elongases: structure, function, and implications in physiology and pathology

Xiangyu Wang,
Hao Yu,
Rong Gao
et al.

Abstract: Background The very-long-chain fatty acid elongase (ELOVL) family plays essential roles in lipid metabolism and cellular functions. This comprehensive review explores the structural characteristics, functional properties, and physiological significance of individual ELOVL isoforms, providing insights into lipid biosynthesis, cell membrane dynamics, and signaling pathways. Aim of review This review aims to highlight the significance of the ELOVL fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…FA elongases (ELOVL family) catalyze the initial step in adding 2-carbon units to long chain FA to produce very long-chain FA [ 26 ]. In particular, ELOVL2 and ELOVL5 work in concert with the desaturases to produce polyunsaturated FA of increasing chain lengths [ 26 ]. Elovl2 mRNA levels in w.t.…”
Section: Resultsmentioning
confidence: 99%
“…FA elongases (ELOVL family) catalyze the initial step in adding 2-carbon units to long chain FA to produce very long-chain FA [ 26 ]. In particular, ELOVL2 and ELOVL5 work in concert with the desaturases to produce polyunsaturated FA of increasing chain lengths [ 26 ]. Elovl2 mRNA levels in w.t.…”
Section: Resultsmentioning
confidence: 99%
“…These pathways involved the concerted action of many key enzymes. To test if the LPC and LPE phenotype in Tet1 mutant cortices can be explained by the gene changes, we performed Gene Set Enrichment Analysis (GSEA) with a list curated genes involved in LPC and LPE biosynthesis [ 66–72 ]. We observed that LPC and LPE genes are positively enriched in Tet1 HxD’s ranked gene set (Normalized Enrichment score (NES): 1.098, FDR q-value: 0.401) and conversely negatively enriched in Tet1 KO’s ranked gene set (NES: −0.650, FDR q-value: 0.929), although they did not meet the statistical FDR cut-off (Figure S4E).…”
Section: Resultsmentioning
confidence: 99%
“…This led to the proposal that GM3 (d18:1-h24:1) be used for metabolic screening [ 127 ]. For cells to have the very-long-chain fatty acids identified in the ceramide components of GM3, cellular very-long-chain fatty acid (VLCFA) elongases (ELOVL1-7) had to catalyze the elongation of the typical fatty acids synthesized [ 128 ]. In the early stages of metabolic syndrome, there is an increase in proinflammatory VLCFAs (22:0, 23:0, 24:0, h24:0) in serum and adipose tissue [ 129 ].…”
Section: Contribution Of Glycan and Ceramide To Gg Functionmentioning
confidence: 99%
“…The effect of this change on GG function remains unknown. Human milk [133] Primarily C24:0,24:1, shorter chains not effective [106], predominantly ≥ C20 [133] d18:1 > d20:1 in human milk [133] Outside-in signaling [106,134]; skin problems, atherosclerosis, mitochondrial disfunction [135] GM3 H 1 : adipose, muscle, liver + serum [127,129]; mature outer retina [136] Primarily C18,22,24,24:1 w9 [137] d18:1 [137,138] d20:1 predominant in pyramidal and granular layers of the dentate gyrus [139] Type 2 diabetes, metabolic disease, and innate immune response [127][128][129] GD3 Prevalent in neuronal stem cells [140] Plasma membrane cytoplasm, ER-mitochondria-associated membranes [141] Longer-chain fatty acids > C18:0 in adult human brain [142] d18:1 > d20:1 Enhances proliferation via its roles in signal transduction (for a review, see [143])…”
Section: Contribution Of Glycan and Ceramide To Gg Functionmentioning
confidence: 99%